IMPLEMENTASI PENDIDIKAN KARAKTER SELAMA PANDEMI COVID-19 DI SEKOLAH DASAR - Agustinus Tanggu Daga (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Educational activities during the Covid-19 pandemic have undergone many changes, including character education for elementary school students in Indonesia. These changes affect the design of the assessment of character education. The problem in this research is how to implement character education during the Covid-19 pandemic in elementary schools. This research aims to describe the implementation of character education in elementary schools during the Covid-19 pandemic. The data collection technique is a documentation study. Data analysis techniques include data reduction, data display, conclusion drawing. The results of this research include the implementation of character education, character values, character education strategies, evaluation of character education, the role of teachers and parents. This research concludes that character education is needed by students and is carried out by teachers. Teachers carry out character assessments and are adapted to the conditions of covid-19 and the real situation of students. The dominant character values implemented are religious values, and values relevant to the Covid-19 condition such as health, caring, tolerance, responsibility, etc. The online learning media used are WhatsApp, activity videos, video calls, zoom, google form. Teachers and parents share roles and work together in carrying out the learning process and character education at home.